(untitled) (Research, Society and Development, 2022)
To analyze the symptoms and quality of life of climacteric women treated in primary health care. Analytical, cross-sectional and quantitative study, carried out in a Basic Health Unit in the rural area of ​​the municipality of Buriti dos Montes-PI. The sample was based on the number of women registered at the UBS aged between 40 and 65 years. Women who had been oophorectomized or who were using Hormone Replacement Therapy were excluded from the study. For data collection, a questionnaire addressing the socioeconomic characterization of the research participants and another questionnaire addressing the quality of life of climacteric women (Women’s Health Questionnare) were used. The research followed the standards of ethics in research related to human beings. The average age of the women was 55 years old, married, multiparous, mixed-race, with a family income of less than 1 minimum wage. They were overweight and most were at high risk for metabolic complications. The mean age at menarche was 13.15 years and at menopause 46.51 years. Most of the research participants used some medication with a higher incidence of antihypertensive drugs, did not perform physical activity and were sexually active. The complaints that most affected the participants were back and limb pain, hot flashes and night sweats. The domain that most compromised the quality of life of climacteric women was vasomotor symptoms. The quality of life of climacteric women is affected by the climacteric syndrome.